Realization and characterization of carbon black based fractional order element. (December 2018) - Biswas, K.; Caponetto, R.; Di Pasquale, G.; Graziani, S.; Pollicino, A.; Murgano, E.
Abstract: In this papers the possibility of realizing fractional capacitors by using carbon black nanostructured dielectrics is investigated. Capacitors have been realized by varying the percentage of distributed carbon black. The frequency analysis of the capacitors has been, therefore, performed. The Bode diagrams outline that this class of devices shows a non integer order behavior. Moreover, a dependance between the curing temperature and the fractional order has been shown.